Influências na Decisão do Jovem Trabalhador Rural Partir ou Ficar no Campo - Fernando Panno (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2014)
The article discusses an issue that is worrying political leaders, academic and community linked to the process of rural development. The gradual disaffection of young children of small farmers to stay on the field is debated worldwide and has been the target of constant attempts of interventions, some successful, but in most practical triggering without noticeable. This study considers three cases of young people of the region of Frederico Westphalen, northwestern Rio Grande do Sul, and involves factors that influence the decision making of these. These decisions, when inserted in the rural regional character gain a broadened and show a tendency to (mis) characterization of the scenario that goes beyond the territorial boundaries, influenced by larger perspectives, involving an economic character as a whole. The three young men, the study focuses, have a university degree, are children of small farmers who are productive and well structured economically and, for various reasons, presented here, are taking different paths in their lives: one of them decided to start a family and remain the property of the parents , associating with other activities on the property, obtaining pluriativity income, another decided to leave for the city, losing temporary interest in the property and the third has decided to return to the parental property, leaving a promising career in the city to become rural entrepreneurs. The data collected in the field, the particularities of the region and support literature have originated this article.